Acceptability of adaptive-learning system based on knowledge-level - Vianny Tobing (2009)
Adaptive E-Learning (AEL) based on students' knowledge-level contributes many benefits to its users. The study on such system is vital as currently, most AEL only consider student's preferences, interest, and navigation behaviour when investigating student's behaviour for personalized services. Further, compared to previous studies on AEL system, user's acceptance towards this type of system, however, has not been assessed and understood thoroughly. In order to get more experience about the acceptance of AEL system that tailored learning content based on students' knowledge-level, a survey consisting of 314 students have been conducted. Based on the Technology Acceptance Model (TAM), this study proposed a conceptual model of AEL system acceptance. The result of regression analysis shows a positive indication on the acceptance of AEL system among students with adaptability feature within the system affect student's intention to use the system. The study provides insight into the usefulness of an AEL system based on students' knowledge-level and gives more intensive view of the AEL system users. It is an important step towards a better understanding of the user's intention on using the system in the future.